Studi Normatif: Efektivitas Dan Keadilan Sosial Dalam Peraturan Hukum Pidana Narkotika di Indonesia - Mayanita, Ulfa; Zulfiko, Riki (DOKTRINA: JOURNAL OF LAW, 2024)
Drug abuse is a serious issue in Indonesia despite being regulated by law. Despite strict law enforcement efforts, including the death penalty for offenders, drug abuse remains rampant. This studi aims to examine the effectiveness and social justice of narcotics criminal law regulations in Indonesia. Through a normative approach, this study uses library research data and qualitative analysis. The result show that although the number of drug cases continues to increase, strict law enforcement has not been fully successful in addressing this issue. Additionally, narcotics criminal law enforcement policies have not always refelected the principle of social justice, particularly in term of rehabilitation and treatment of offenders. A more restorative justice approach is needed to addres this problem. This approach will emphasize rehabilitation, social reintegration, and prevention of drug abuse rather than focusing solely on punishment. Thus, it is hoped that more effective and just solutions can be achived in addressing the drug problem in Indonesia.